The Status of Wildlife Damage Compensation in China - Wenxia Wang; Torsten Wronski; Liangliang Yang (Animals, 2024)
The conservation management of natural ecosystems in China has significantly improved in recent decades, resulting in the effective protection of wildlife and the restoration of habitats. With the rapid growth in wildlife populations and corresponding range expansions, incidents of human–wildlife conflict have notably increased across China. However, only a few studies have paid adequate attention to wildlife damage management and compensation. In our review, we focus on the foremost mitigation measure to combat human–wildlife conflict, i.e., compensation for damage caused by wildlife. We conducted a questionnaire survey and an in-depth review of the literature across 19 Chinese provinces and autonomous regions, resulting in a total of 78 relevant sources. We first introduce the concept of wildlife damage compensation in China, followed by a review of Chinese legislation and policies regarding wildlife damage compensation. We compiled a comprehensive list of nuisance species, and we showcase four case studies in which we exemplarily describe the current situation of wildlife damage compensation. We reflect on difficulties and challenges such as delayed damage assessments or compensation quotas that do not correspond to current market prices. Since local legislation is often insufficient or completely absent, we make suggestions on how to improve existing policies and compensation mechanisms.